1998
DOI: 10.1007/pl00005254
|View full text |Cite
|
Sign up to set email alerts
|

Specific interaction of 5-HT-moduline with human 5-HT1b as well as 5-HT1d receptors expressed in transfected cultured cells

Abstract: 5-HT1B receptors are the predominant auto- and heteroreceptors located on serotonergic and non-serotonergic terminals where they regulate the neuronal release of neurotransmitters. 5-HT-moduline (Leu-Ser-Ala-Leu) has been shown to specifically interact with a very high apparent affinity and in a non-competitive manner with 5-HT1B receptors (Massot et al. 1996; Rousselle et al. 1996). Using transfected cells expressing either 5-HT1B or 5-HT1D receptors, it was shown that 5-HT-moduline prevents the binding of [3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…1). The fact that ALLS, a peptide having the same structure as LSAL in a different sequence, was inactive supports the view that the effect is specific for LSAL (5-HT moduline) as already reported in previous studies (Massot et al 1996;Rousselle et al 1998;Seguin et al 1997). The antagonistic effect of 5-HT moduline was shown at concentrations (100 nM) higher than those corresponding to the apparent binding affinity (<1 nM; Massot et al 1996); this could be related to its rapid degradation under the experimental conditions used whereas binding experiments of 5-HT moduline to brain homogenate were performed at 4°C, which decreased the degradation of the peptide (Massot et al 1996).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…1). The fact that ALLS, a peptide having the same structure as LSAL in a different sequence, was inactive supports the view that the effect is specific for LSAL (5-HT moduline) as already reported in previous studies (Massot et al 1996;Rousselle et al 1998;Seguin et al 1997). The antagonistic effect of 5-HT moduline was shown at concentrations (100 nM) higher than those corresponding to the apparent binding affinity (<1 nM; Massot et al 1996); this could be related to its rapid degradation under the experimental conditions used whereas binding experiments of 5-HT moduline to brain homogenate were performed at 4°C, which decreased the degradation of the peptide (Massot et al 1996).…”
Section: Discussionsupporting
confidence: 78%
“…The endogenous peptide, 5-HT moduline (LSAL), has been recently demonstrated to be a selective non-competitive 5-HT 1B/1D receptor antagonist, probably acting as an allosteric modulator of the 5-HT 1B/1D receptor protein (Massot et al 1996;Rousselle et al 1998). Preincubation of the rat striatal synaptosomes with various concentrations of 5-HT moduline significantly reduced the effect of CP93,129 on the K + -overflow of [ 3 H]DA in a non-competitive manner (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro pharmacology profile for unlabeled P943 is shown in Table 1, demonstrating its potency and selectivity towards 5-HT 1B ; however, no assay was performed for its selectivity towards 5-HT 1B vs. 5-HT 1D as there is no drug selective only for 5-HT 1B or 5-HT 1D. GR 127,935 is a potent and effective antagonist for human 5-HT 1D and 5-HT 1B with a pKi value of 9.0 and 8.6 for 5HT 1B and 5HT 1D , respectively [27,28,29]. In our blocking study with GR 127,935, a near complete blockade of [ 11 C]P943 binding was observed after pretreatment with GR 127,935.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the CP-93129-induced inhibition was reduced 1) by pretreatment with a specific polyclonal 5-HT 1B receptor antibody directed against a region of the receptor protein involved in signal transduction and 2) by pretreatment with 5-HT moduline, a tetrapeptide with the amino acid sequence LSAL (Sarhan et al, 2000). This endogenous peptide was shown to be a selective noncompetitive 5-HT 1B/1D antagonist, probably acting as an allosteric modulator of the 5-HT 1B receptor protein (Massot et al, 1996;Rousselle et al, 1998). It is also compatible with the 5-HT 1B character of the presynaptic 5-HT heteroreceptor that G i /G o proteins appear to be involved in signal transduction, as suggested by the attenuation of the inhibitory effects of 5-HT 1B receptor agonists by pertussis toxin (Sarhan and Fillion, 1999), Inhibitory presynaptic 5-HT 1B receptors on dopaminergic nerve terminals have also been shown in the mouse striatum by application of the same elegant approach as in the rat striatum: the K ϩ -evoked [ 3 H]DA release was inhibited by CP-93129 from mouse striatal synaptosomes and this effect was sensitive to blockade by SB 224289 (Sarhan et al, 2000).…”
Section: Presynaptic 5-hydroxytryptamine 1bmentioning
confidence: 99%